A founder nonsense variant in NUDT2 causes a recessive neurodevelopmental disorder in Saudi Arab children. Issue 3 (30th July 2018) - Yavuz, H.; Bertoli‐Avella, A.M.; Alfadhel, M.; Al‐Sannaa, N.; Kandaswamy, K.K.; Al‐Tuwaijri, W.; Rolfs, A.; Brandau, O.; Bauer, P.
Abstract : We identified the homozygous p.Arg12* variant in 5 patients with neurodevelopmental delay, but variation databases list many truncating heterozygous variants for this small 2‐exon gene. As most of these affect the protein's C‐terminus, loss‐of‐function mediated pathogenicity may be confined to bi‐allelic truncating variants in exon 1 (nonsense‐mediated decay!) or in the catalytically active Nudix box.